Changes in Plasma Levels of N-Arachidonoyl Ethanolamine and N-Palmitoylethanolamine following Bariatric Surgery in Morbidly Obese Females with Impaired Glucose Homeostasis. (22nd March 2015) - Mallipedhi, Akhila; Prior, Sarah L.; Dunseath, Gareth; Bracken, Richard M.; Barry, Jonathan; Caplin, Scott; Eyre, Nia; Morgan, James; Baxter, John N.; O'Sullivan, Saoirse E.; Sarmad, Sarir; Barrett, David A.; et al.
Abstract : Aim . We examined endocannabinoids (ECs) in relation to bariatric surgery and the association between plasma ECs and markers of insulin resistance. Methods . A study of 20 participants undergoing bariatric surgery. Fasting and 2-hour plasma glucose, lipids, insulin, and C-peptide were recorded preoperatively and 6 months postoperatively with plasma ECs (AEA, 2-AG) and endocannabinoid-related lipids (PEA, OEA). Results . Gender-specific analysis showed differences in AEA, OEA, and PEA preoperatively with reductions in AEA and PEA in females postoperatively. Preoperatively, AEA was correlated with 2-hour glucose (r = 0.55, P = 0.01 ), HOMA-IR (r = 0.61, P = 0.009 ), and HOMA %S (r = - 0.71, P = 0.002 ). OEA was correlated with weight (r = 0.49, P = 0.03 ), waist circumference (r = 0.52, P = 0.02 ), fasting insulin (r = 0.49, P = 0.04 ), and HOMA-IR (r = 0.48, P = 0.05 ). PEA was correlated with fasting insulin (r = 0.49, P = 0.04 ). 2-AG had a negative correlation with fasting glucose (r = - 0.59, P = 0.04 ). Conclusion . Gender differences exist in circulating ECs in obese subjects. Females show changes in AEA and PEA after bariatric surgery. Specific correlations exist between different ECs and markers of obesity and insulin and glucose homeostasis.